THE ESSENTIAL OIL CONTENTS OF JERINGAU (Acorus calamus L.) RHIZOMES AND THEIR ANTIFUNGAL ACTIVITY AGAINST Candida albicans - Rita, Wiwik Susanah; Kawuri, Retno; Swantara, I Made Dira (Journal of Health Sciences and Medicine; Vol 1 No 1 (2017): JHSM (Febuary 2017)DO - 10.24843/JHSM.2017.v01.i01.p09, 2017)
Acorus calamus L. rhizome was trusted having antibacterial activity. This study aimed to identify the compounds in the Acorus Calamus L. rhizomes essential oils and to recognize the antifungal activity of the oils against Candida albicans. The extraction of essential oils from rhizome was carried out by steam distillation technique. Identification of compounds in the oils was conducted by Gas Chromatography- Mass Spectroscopy (GCMS), while the antifungal test against Candida albicans was done by well diffusion method. Extraction of 10 kg of rhizomes produced 16.53 mL essential oil with a yield of 0.1653% (? = 1.066), the oil was brownish yellow and very flavorful. GC-MS analysis showed that the essential oil contained 11 compounds, they are (E)-3,7 dimethyl-1,3,6-Octatriene (trans-?-Ocimene) (3,73%), linalool (1,07%), ?-elemene (1,15%), trans methyl isoeugenol (7,68%), shyobunon (15,74%), bicyclogermakren (0,93%), dehidroxy-isocalamendiol (2,61%), ?-calacorene (3,34%), euasarone (26,84), cis-asarone (18,62%); dan trans- asarone (18,29%). Antifungal activity test showed that the growth and biomass inhibition of C. albicans increased with the increase of the oil concentration. Minimum Inhibitory Concentration (MIC) of essential oil toward C. albicans was 1% with the inhibition of 7.83 mm.